P375 Faecal calprotectin variation after induction therapy with infliximab to predict clinical, endoscopic and ultrasonographic remission in Crohn's disease patients. (21st January 2022) - Revés, J; Morão, B; Gomes, C F; Nascimento, C; Abreu, N; Gonçalves, T C; Castro, F; Freitas, M; Moreira, M J; Cotter, J; Pereira, F; Caldeira, A; et al.
Abstract: Background: Faecal calprotectin (FCal) is considered an intermediate target for monitoring disease activity in IBD. However, it is unknown whether early FCal variations during induction therapy may be a significant predictor of treatment response. We aimed to investigate FCal variation after infliximab induction therapy and its association with clinical, endoscopic, and ultrasonographic remission by the end of one year of treatment. Methods: Prospective multicentric cohort study including patients with active CD without previous intestinal surgeries, who were starting IFX therapy and were followed for, 54 weeks. FCal was measured at week, 0 and after induction therapy (week, 14) and relative FCal changes from baseline (%FCal0-14 ) were calculated. At week, 54, clinical remission (defined as Harvey-Bradshaw index (HBI) <5), endoscopic healing (defined as SES-CD score <3) and transmural healing (defined as bowel wall thickness (BWT) assessed by intestinal ultrasound (IUS) ≤3mm) were evaluated. Results: We included, 33 patients (60.6% male; median age, 30 years old (IQR, 24–42)). Most patients were diagnosed between, 17–40 years old (75.8%) had ileocolonic disease (57.6%) and an inflammatory phenotype (57.6%). At week, 54, 90.9% of the patients were in clinical remission, 30.3% had endoscopic healing and, 39.4% had transmural healing. The median FCal value at week, 0 was, 765µg/g (IQR, 312–1313) and at week, 14 was, 124.5µg/g (IQR, 46–432.5). At week, 14, 20 patients (60.6%) had FCal<250µg/g. There was no correlation between FCal at week, 0 and the baseline total SES-CD (r=0.28, p=0.13) and BWT of the most affected segment (r=0.02, p=0.90). Patients who achieved clinical remission had a low variation in %FCal0-14 (87.4% vs, 80.1%, p=0.42), as opposed to patients who achieved endoscopic healing (58.5 vs, 91.3%, p<0.001) and transmural healing (68.6% vs, 84.4%, p=0.16) who had more significant changes in %FCal0-14, although only statistically significant for endoscopic healing. When stratifying %FCal0-14 changes in, 25% quartiles, FCal variation at the end of induction was only able to predict endoscopic healing (OR, 8.13 (95%CI, 1.01–65.46), p=0.049), being non-significant for clinical remission (OR, 0.51 (95%CI, 0.09–2.92), p=0.45) and transmural healing (OR, 1.61 (95%CI, 0.73–3.57), p=0.24). A normalization of FCal below, 250 µg/g was also a predictor of endoscopic healing (OR, 9.82 (95%CI, 1.06–90.59), p=0.04). The AUC for the prediction of endoscopic healing with %FCal0-14 changes was, 0.85 (Figure, 1) and a cut-off of variation of, 80.3% was calculated. Conclusion: FCal variation at the end of induction seems to be a good predictor of endoscopic healing at week, 54 but does not seem to be able to predict clinical and ultrasonographic remission.